Human Capital and Climate Change - Noam Angrist; Kevin Winseck; Harry A. Patrinos; Joshua Graff Zivin (Institute of Labor Economics (IZA), 2023)
Addressing climate change requires individual behavior change and voter support for pro-climate policies, yet surprisingly little is known about how to achieve these outcomes. In this paper, we estimate causal effects of additional education on pro-climate outcomes using new compulsory schooling law data across 16 European countries. We analyze effects on pro-climate beliefs, behaviors, policy preferences, and novel data on voting for green parties – a particularly consequential outcome to combat climate change. Results show a year of education increases pro-climate beliefs, behaviors, most policy preferences, and green voting, with voting gains equivalent to a substantial 35% increase.
Keywords: D72; H41; I20; I28; P16; Q01; Q5; 330; human capital; education; climate change; compulsory schooling laws; voting